Reference values of fetal pulmonary artery branch from 18 to 40 weeks of gestation - Sasiwimon Phuakpoolpol; Thotsapon Trakulmongkichkarn; Sanpon Diawtipsukon; Saowapak Junhasavasdikul (Scientific Reports)
Abstract The information and the reference values determined by gestational age of pulmonary vascular resistance parameters of the branch pulmonary arteries measured by Doppler ultrasonography are quite scarce. The authors define the parameter values of the branch pulmonary artery and correlate them with the gestational age. We recruited 160 singleton pregnant women, gestational ages between 18 and 40 weeks, who took antenatal care at Phramongkutklao Hospital, Bangkok, Thailand. The fetal echocardiography was performed on all of the participants, and the measurements were obtained from the diameters, acceleration-to-ejection time (AT/ET) ratio, peak early-diastolic reversed flow (PEDRF), and pulsatility index (PI) from the right and left pulmonary artery branches. All parameters were analyzed to be used as the reference ranges and correlated with gestational age. All the participants delivered at term gestational age (38 ± 1.2 weeks) without congenital cardiac anomalies. The branch pulmonary artery diameter and PEDRF significantly increased with gestational age (P-value < 0.001). In contrast, the other branch pulmonary artery parameters were unrelated. Branch pulmonary artery diameter and PEDRF can be used as a reference value. The abnormal decrease in branch pulmonary artery diameter and PEDRF may predict the abnormality of pulmonary vasculature development.